DNA sequence of histidine-3 from two Neurospora wild-types. - P J Yeadon; A PETERSEN; David E A CATCHESIDE (Fungal Genetics Reports, 1998)
We report sequence differences between laboratory strains of Neurospora within his-3,and corrections to published sequence for this locus for ST74A strains, of possible significance to experiments using histidine mutants for gene replacement and gene targeting.